Etničnost i etničke manjine u Hrvatskoj - Čačić-Kumpes, Jadranka (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2006)
ETHNICITY AND ETHNIC MINORITIES IN CROATIA: AN OUTLINE OF THE SITUATION AND RESEARCH PERSPECTIVES. The paper presents an overview of research on ethnicity and on ethnic minorities in Croatia from the early 1990ćs until the most recent years at the turn of this century. The authors first review definition sand understandings of the concepts of minority and of ethnicity in the research context, as well as some aspects pertaining to the influence of the social context on researchers and on their approach to the subject and, consequently, to their research. Next, using a simple form of thematic content analysis, research themes in the framework of ethnic and minority topics from the early 1990's until 2005 are initially systematised, according to scientific disciplines and research institutions dealing with these themes. Based on their examination of the main research themes, the authors give an outline of the situation (the multidisciplinary approach, critical analysis of minority rights, critical examination of nationalism, discourse focused on cultural pluralism and diversity, a prevalently dynamic understanding of culture, ethnicity and identity) and indicate some new perspectives in regard to ethnic and minority research in Croatia at the start of the 21st century.
Keywords: Croatia; Hrvaška; narodne manjšine; etnična struktura; raziskovanje; nationalism; nacionalizem; zgodovinski pregledi